MINIMALISASI OVERBREAK DAN UNDERBREAK MELALUI PEMODELAN PREDIKTIF DAN OPTIMASI PELEDAKAN PT FREEPORT INDONESIA - Rochsyid Anggara; Bantar Tyas Suksmawati Rukmana; Rayhan Naufal Pratama; Jeffryson Munsaki Rumbewas (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2025)
Blasting activities in the development of underground openings at the Kucing Liar (KL) Mine, PT Freeport Indonesia, may cause geometric deviations in the form of overbreak and underbreak. Evaluation of blasting performance in November 2024 indicated that, in several headings, geometric deviations exceeded the company’s tolerance limit of 10%, highlighting the need for blasting parameter optimization. This study aims to control overbreak–underbreak through the development of predictive models based on geotechnical and blasting parameters. Multiple Regression Analysis (MRA) was applied to 53 blasting records using Rock Mass Classification (Q-value), Perimeter Powder Factor (PPF), and Confinement Factor (C) as independent variables. The novelty of this study lies in the integration of multivariate regression models derived from operational data with Monte Carlo simulation to provide probabilistic and practical blasting parameter optimization. The regression models were subsequently used in a Monte Carlo simulation with 5,000 iterations. The results indicate that overbreak is significantly influenced by Q-value, PPF, and Confinement Factor (R² = 0.693), whereas underbreak is predominantly controlled by Q-value (R² = 0.470). Monte Carlo simulation reduced the average overbreak to 7.41% and resulted in an average underbreak of 5.37%, both of which are below the company’s tolerance threshold.